Zn-Mediated Hydrodeoxygenation of Tertiary Alkyl Oxalates - Ye, Yang; Ma, Guobin; Yao, Ken; Gong, Hegui (Synlett, 2021)
Herein we describe a general, mild, and scalable method for hydrodeoxygenation of readily accessible tertiary alkyl oxalates by Zn/silane under Ni-catalyzed conditions. The reduction method is suitable for an array of structural motifs derived from tertiary alcohols that bear diverse functional groups, including the synthesis of a key intermediate en route to estrone.
Keywords: Zn; silane; hydrodeoxygenation; C–O bonds; oxalates